Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes. (1st May 2023) - Gao, Juan; Wei, Xian-Yong; Kang, Yu-Hong; Zhang, Xiao-Qi; Wang, Ai-Min; Li, Xia-Long; Gao, Yong; Liu, Guang-Hui; Chen, Tao; Li, Yan-Jun; Ma, Xiang-Rong; Bai, Jin-Jun; et al.
Highlights: 10 %Ni/MZB exhibits high activity for cleaving > C-X bonds and hydrogenating aromatic ring during CHC. DFT calculations indicate that the H +, H −, and H…H from 10 %Ni/MZB is great important in CHC. 10 %Ni/MZB has synergistic effects of strong LASs and non-noble metal Ni NPs during CHC. All of group components in EPJSBC were completely converted to cycloalkanes and hydroarenes. Abstract: The catalytic hydroconversion (CHC) of heavy carbon organic species (HCOSs) to cycloalkanes represents an importantly used chemical industry process due to the wide applicability of the resulting products in energy and fine chemistry. Despite the existing conventional catalysts applied to the CHC of HCOSs, the development of highly active bifunctional Ni-based heterogeneous catalysts for this process is still a challenge. Therefore, we show that the modified deposition–precipitation of nickel (II) nitrate on hydrothermally synthesized mesoporous zeolite Beta (MZB) prepares a Ni/MZB catalyst with a through-crosslinking mesopore structure and uniformly disperse Ni nanoparticles (NPs) at rough MZB crystal surface. The 10%Ni/MZB (10% Ni loading), in the presence of exposing on amount of accessible Lewis acid sites (LASs) and attaching Ni NPs by chemical bonding from the silica matrix of MZB skeleton, exhibits excellent activity to promote the CHC of all kind of aromatic rings and heteroatom-containing species, including chain alkanes, arenes, oxygen-containing organic compounds (OCOCs), nitrogen-containing organic compounds (NCOCs), and sulfur-containing organic compounds (SCOCs), to produce cycloalkanes and hydroarenes under mild conditions. Interestingly, density functional theory (DFT) calculations indicate that the transfer of biatomic active hydrogen (H … H) and heterogenous H + from 10%Ni/MZB plays important roles during the CHC of diphenoxybenzene (DPOB). After being recycled 4 times, 10%Ni/MZB is still maintains high activity for CHC of DPOB under mild conditions.